Reações de Etanol com CO/H2 na Presença do Sistema Catalítico Ru(acac)3/I- - Trabuco, Elizeu [UNESP] (Sociedade Brasileira de Química, 1997)
The hydrocarbonylation reaction of ethanol with a CO/H2 mixture assisted by Ru(acac)3/iodide was investigated. Bronsted and Lewis acids and iodides salt were used as homogeneous promoters. The etherification reaction was the main reaction under typical acidic conditions of the catalytic system. When a hydrocarbon solvent (toluene) was added to the initial reaction, the alcohol conversion and the carbonylation products were increased. The catalytic activity of the Bronsted acids (conv. EtOH = 71-92%) was higher than that of the Lewis acids promoters (conv. EtOH = 65-85%). The salt present the lower catalytic activity among the promoters used. The long time reaction carried out with ethanol showed an increase of the product selectivity of the homologation and carbonylation reactions while the etherification reaction selectivity decreased. The recycled ether led to 60-65% ethanol conversion to C5 and C6 products. The main catalytic species are H+[Ru(CO)3I3]-, [HRu3(CO)11]- and [HRu(CO)4]-. The first one is active in the carbonylation and homologation reactions of alcohols while the two others take part only in the homologation reaction.
Ethanol, reactions with co/h2 in the presence of the ru(acac)3/i- catalytic system
Keywords: Ethanol; hydrocarbonylation; ruthenium; catalysis